2019
DOI: 10.7575/aiac.abcmed.v.7n.2p.44
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Resveratrol in Gliomas

Abstract: Resveratrol (RSV) is found in most human foods especially fruits such as grapes, peanuts, strawberry, blueberry, cranberry, mulberry, lingberry, sparkleberry, bilberry and in flowers as well as leaves like butterfly orchid tree, eucalyptus, spruce, lily, gnetum and so many others. Functionally, RSV has the propensity to safeguard DNA as well as the induction of DNA repair. RSV is precipitously metabolized in the liver via phase-II detoxification enzymes leading to its principal urine excretion. RSV steered gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 125 publications
(237 reference statements)
0
12
0
Order By: Relevance
“…The authors demonstrated the inhibition of the expression of specific oncogenic microRNAs (miRs) such as miR-21, miR-19, and miR-30a-5p in glioma cells, which was consequently associated with altered expression of their targeting genes such as p53, STAT3, EGFR, COX-2, NF-κB, and the PI3K/AKT/mTOR signaling pathway. Moreover, RES suppressed tumor growth and prolonged survival of rats bearing intracranial C6 glioma [145]. Induction of S-G2/M cell cycle arrest by RES was also described in human GBM cell lines and was accompanied by an increase in levels of pCdc2(Y15), cyclin A, E, and B and a decrease of cyclin D1 [149].…”
Section: Antiproliferative and Proapoptotic Effects Of Resveratrolmentioning
confidence: 78%
See 2 more Smart Citations
“…The authors demonstrated the inhibition of the expression of specific oncogenic microRNAs (miRs) such as miR-21, miR-19, and miR-30a-5p in glioma cells, which was consequently associated with altered expression of their targeting genes such as p53, STAT3, EGFR, COX-2, NF-κB, and the PI3K/AKT/mTOR signaling pathway. Moreover, RES suppressed tumor growth and prolonged survival of rats bearing intracranial C6 glioma [145]. Induction of S-G2/M cell cycle arrest by RES was also described in human GBM cell lines and was accompanied by an increase in levels of pCdc2(Y15), cyclin A, E, and B and a decrease of cyclin D1 [149].…”
Section: Antiproliferative and Proapoptotic Effects Of Resveratrolmentioning
confidence: 78%
“…It has been demonstrated that RES is a radiation sensitizer for highly radioresistant human SU-2 glioma stem cells. The synergistic effect of RES and radiation was seen in the inhibition of cell proliferation, induction of autophagy, promotion of apoptosis, prevention of DNA repair in the early stage, and induction of differentiation, both in vitro and in vivo [145].…”
Section: Resveratrol and Standard Anticancer Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…Resveratrol (3,4′,5-trihydroxy-trans-stilbene) anti-cancer effects include anti-proliferation, cell cycle arrestment, and apoptosis promotion through multiple signaling pathways such as EGFR, p53, P13K/AKT/mTOR, STAT3, NF-κB, and oncogenic miRNAs [ 296 , 297 ]. Resveratrol suppresses tumor growth and prolongs survival in rats bearing intracranial C6 glioma [ 296 , 298 , 299 ]. Wang and coworkers showed a longer mean survival in C6-xenograft rats treated with resveratrol (29.75 ± 9.27 days) than the control group (15.8 ± 0.93 days) [ 296 ].…”
Section: Phytochemicals and Nanoparticles In Hggmentioning
confidence: 99%
“…The RG7388/RT combination is also included in a phase I/IIa trial in patients with newly diagnosed GB without O(6)-methylguanine-DNA methyltransferase (MGMT) promotor methylation (N²M² (NOA-20), NCT03158389). Nutraceutical resveratrol, which has been reported to induce p53 and its downstream targets, acted as a radiosensitizing anticancer agent for highly radioresistant human SU-2 GSC both in vitro and in vivo ( 143 , 144 ).…”
Section: Mdm2 Inhibitors As Radiosensitizersmentioning
confidence: 99%